2022
DOI: 10.28991/esj-2022-sper-014
|View full text |Cite
|
Sign up to set email alerts
|

Ratification of ICRMW toward the ILO Conventions amid COVID-19 in Thailand

Abstract: Globalization has opened the avenues for the world to come together and attain sustainable growth. Migrant workers are a lifeline for several countries' labour forces and productivity. However, in Thailand, the rights of these migrants are restricted due to the non-ratification of the International Convention on the Protection of the Rights of Migrant Workers and Family Members (ICRMW). This research explores and analyzes various factors essentially responsible for the ratification of ICRMW in Thailand. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…To control COVID-19, individuals must intend to prevent and fight against it. The intention to prevent COVID-19 refers to the public's adoption of preventive measures to control the spread of the disease [19].…”
Section: Research Hypothesesmentioning
confidence: 99%
“…To control COVID-19, individuals must intend to prevent and fight against it. The intention to prevent COVID-19 refers to the public's adoption of preventive measures to control the spread of the disease [19].…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Nearly all studies across the world reported on the reduction in work and income for individuals involved in sex work during the COVID-19 pandemic (Aantjes et al, 2023;Azam et al, 2021;Burgos & Del Pino, 2021;Cabras & Ingrasci, 2022;Callander et al, 2022;Chakrapani et al, 2022;Fedorkó et al, 2022;Gbagbo, 2020;Hassan et al, 2023;Judge & Jackson, 2023;Kahambing, 2021;Kavanagh et al, 2021;Laikram & Pathak, 2021;Leyva-Moral et al, 2023;Lamontagne et al, 2022;Machingura et al, 2021;Magnani et al, 2022;Mantell et al, 2021;Matambanadzo et al, 2021;Mlambo & Masuku, 2022;Moura et al, 2022;Museva et al, 2021;Nyabeze et al, 2022;Pearson et al, 2022;Pereira, 2021;Pollard et al, 2021;Richterman et al, 2022;Santos et al, 2022;Shankar et al, 2022;Shekhar, 2023;Singer et al, 2020;Su & Valiquette, 2022;Tan et al, 2021aTan et al, , 2021bTran et al, 2022;Wang et al, 2022;Wirawan et al, 2022).…”
Section: Reduction In Work and Incomementioning
confidence: 99%
“…Reduced work and subsequent reduced income left sex workers in many studies across the world facing housing insecurity (Benoit & Unsworth, 2022;Burgos & Del Pino, 2021;Cabras & Ingrasci, 2022;Callander et al, 2022;Dziuban et al, 2021;Gichuna et al, 2020;Hassan et al, 2023;Laikram & Pathak, 2021;Lamontagne et al, 2022;Leyva-Moral et al, 2023;Moura et al, 2022;Pollard et al, 2021;Rogers et al, 2021;Tan et al, 2021aTan et al, , 2021bTran et al, 2022). Housing was threatened not only by lost income but by the loss of access to motels and short-term rentals (Callander et al, 2022) suggesting the pandemic may have disproportionately affected those of low socioeconomic status who were in unstable housing.…”
Section: Housing Insecuritymentioning
confidence: 99%
See 2 more Smart Citations